2015
DOI: 10.5209/rev_rced.2015.v26.n3.44551
|View full text |Cite
|
Sign up to set email alerts
|

Predictores de las actitudes hacia la inclusión de alumnado con necesidades educativas especiales en futuros profesionales de la educación

Abstract: Predictores de las actitudes hacia la inclusión de alumnado con necesidades educativas especiales en futuros profesionales de la educaciónPredictors of attitudes toward inclusion of students with special educational needs in future education professionals ResumenUno de los principales pilares en la construcción de escuelas inclusivas es la formación inicial del profesorado. Antes de determinar si es necesario realizar cambios y de qué tipo en los programas formativos o planes de estudios en relación con la at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
3
12
2
16
Order By: Relevance
“…Of the eighteen studies that analyzed the influence of gender, seven found that women tend to be more positive [20][21][22][23][24][25][26] and four found that men have better attitudes [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the eighteen studies that analyzed the influence of gender, seven found that women tend to be more positive [20][21][22][23][24][25][26] and four found that men have better attitudes [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Contact with people with disabilities and/or students with special educational needs seems to positively influence teachers' perception of inclusion, according to eight of the eleven studies that analyzed this aspect [20,23,24,31,[37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, FL teachers do not feel the need to use inclusive teaching methods [50]. Nonetheless, there are studies claiming that a change in the training of pre-service teachers has positive effects in terms of mooting the idea of problematizing the importance of inclusive approaches to linguistic education [51][52][53]. However, although there is a crystal-clear correlation between pre-service teachers' attitudes and linguistic development, there are numerous authors who argue that this positiveness is diluted in practice [52,[54][55][56].…”
Section: Students With Mid In the Fl Classroommentioning
confidence: 99%
“…Hoy en día, un aspecto que caracteriza las aulas españolas es la presencia de un alumnado diverso. Tal y como indican Hinojosa y López (2013) y Álvarez y Buenestado (2015), la diversidad presente en todos los contextos e intrínseca al ser humano se ha visto incrementada por el desarrollo de la tecnología, las posibilidades de movilidad de las personas y por los procesos migratorios. Por este motivo se considera necesario gestionar de forma adecuada la 1 diversidad, asegurando una educación de calidad y libre de prejuicios sociales para todos.…”
Section: Introductionunclassified